Field Test on Performance of an Air Source Heat Pump System Using Novel Gravity-Driven Radiators as Indoor Heating Terminal - Jia, Jie; Zhou, Xuan; Feng, Wei; Cheng, Yuanda; Tian, Qi; Li, Fenglei; Chen, Yanjun; Lee, W.L. (Frontiers in Energy Research, 2021)
The simultaneous need for energy efficiency and indoor comfort may not be met by existing air source heat pump (ASHP) technology. The novelty of this study lies in the use of a new gravity-driven radiator as the indoor heating terminal of ASHPs, aiming to provide an acceptable indoor comfort with improved energy efficiency. To confirm and quantify the performance improvement due to the proposed system retrofit, a field test was conducted to examine the system performance under real conditions. In the tests, measurements were made on the refrigerant- and air-side of the system to characterize its operational characteristics. Results showed that the proposed radiator has a rapid thermal response, which ensures a fast heat output from the system. The proposed system can create a stable and uniform indoor environment with a measured air diffusion performance index of 80%. The energy efficiency of the proposed system was also assessed based on the test data. It was found that the system’s first law efficiency is 42.5% higher than the hydraulic-based ASHP system. In terms of the second law efficiency, the compressor contributes the most to the overall system exergy loss. The exergy efficiency of the proposed system increases with the outdoor temperature and varies between 35.02 and 38.93% in the test period. The research results and the analysis methodology reported in this study will be useful for promoting the technology in search of energy efficiency improvement in residential and commercial buildings.